Methodological basis of supply nuclear energy organizations - E. A. Kirillova; N. A. Uvarova (Путеводитель предпринимателя, 2020)
The article presents the methodological basis for solving the problems of improving the efficiency of nuclear power organizations. The management organization principles of the material and technical support system on the basis of identification and analysis macro - and micrologistic system factors that have a significant impact on the implementation of this business process are described.